COPD Exacerbation History and Impact on Future Exacerbations – 8-Year Retrospective Observational Database Cohort Study from Germany - Vogelmeier CF; Diesing J; Kossack N; Pignot M; Friedrich FW (International Journal of COPD, 2021)
Claus F Vogelmeier,1 Joanna Diesing,2 Nils Kossack,2 Marc Pignot,3 Felix W Friedrich4 1Department of Medicine, Pulmonary and Critical Care Medicine, University Medical Center Giessen and Marburg, Philipps-Universität Marburg, Marburg, Hessen, Germany; 2WIG2 GmbH Scientific Institute for Health Economics and Health System Research, Leipzig, Sachsen, Germany; 3Kantar Health, Munich, Germany; 4AstraZeneca, Wedel, GermanyCorrespondence: Felix W FriedrichAstraZeneca GmbH, Tinsdaler Weg 183, Wedel, D-22880, GermanyTel +49 162 1398835Email felix.friedrich@astrazeneca.comBackground: Recent studies evaluating the predictive value of different variables on future exacerbations suggest exacerbation history as the strongest predictor. We examined the effect of exacerbation history on subsequent events in a large sample population with over 250,000 COPD patients using up to 8 years of longitudinal healthcare data from Germany.Methods: Patients 40 years or older with any COPD diagnosis in primary or secondary care were included from 2011 to 2017 (index period) from healthcare insurance claims (Germany; WIG2 research database), with 12 months before index date as baseline and at least 12-month follow-up. Exacerbations during baseline were defined as moderate (treatment with oral corticosteroids or antibiotics, J01AA, J01CA) or severe (emergency visit or hospitalization).Results: Patients without (category A), with one moderate (category B), or with either one severe or several baseline exacerbations (category C) experienced an average of 0.9 (CI 0.9– 0.9), 1.9 (CI 1.9– 1.9), and 6.3 (CI 6.1– 6.3) exacerbations during the first 3 years of follow-up, respectively. By 8 years, 87.0% (CI 86.6– 87.4), 70.5% (CI 69.9– 71.0) and 49.1% (CI 48.9– 49.3) of category C, B and A patients had experienced a subsequent exacerbation.Conclusion: Baseline exacerbations increased the likelihood of, and reduced time to subsequent exacerbations. Even patients without baseline exacerbations experienced exacerbations within three years, emphasizing the importance of adequate treatment in patients with less severe disease presentation as well.Keywords: chronic obstructive pulmonary disease, COPD, exacerbations, economic burden, healthcare resource utilization